Application of the IEC80001 standard towards integration of a real time alarm communication and management system: A case study. Issue 4 (8th June 2015) - Eckhardt, Kyle; Hayes, Andrew; Hamilton, Michael; Gaamangwe, Tidimogo
Abstract : Purpose: – The purpose of this paper is to report on use of the IEC80001 standard, Application of Risk Management for Information Technolody (IT) Networks Incorporating Medical Devices, to deploy a wireless alarm management solution in a long-term care home facility. Design/methodology/approach: – The standard suggests the use of a unique responsibility matrix and a continuous quality improvement approach for analysis, evaluation and control of risks. A unique leadership committee and workgroup were formed to develop processes and procedures for integrating medical devices with IT systems; as well as execution of the project itself. The leadership committee oversaw the phased approach of assessing the technology, the clinical environment, proponent technology-based solutions and a specified risk management file. The project expanded its scope beyond the standard to include a risk focussed analysis of clinical workflow to evaluate the usability of the solution. Findings: – The standard focussed approach identified numerous risks associated with the technical and network solution and the future state workflow. Medical devices proved to be the most limiting technology needing to be incorporated into the solution. Although faced with a daunting list of network related risks, it was concluded that all residual risks would have been acceptable. The analysis of the future state workflow identified various risks related to usability (human factors), battery management and the absence of additional operating dollars for supplementary staffing duties and new operational expenses. Originality/value: – To the best of the authors knowledge, this paper is the first one to detail the process of following the IEC80001 standard in Canada. It offers insight into building an organizational framework around the standard and identifies gaps that should be considered by executive and project sponsors before proceeding with a project.